Feasibility and Acceptability of An Audio Computer-Assisted Self-Interview Version of the Alcohol, Smoking and Substance Involvement Screening Test (Assist) in Primary Care Patients. Issue 2 (April 2016) - Spear, Suzanne E.; Shedlin, Michele; Gilberti, Brian; Fiellin, Maya; McNeely, Jennifer
Background: This study explores the feasibility and acceptability of a computer self-administered approach to substance use screening from the perspective of primary care patients. Methods: Forty-eight patients from a large safety net hospital in New York City completed an audio computer-assisted self-interview (ACASI) version of the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) and a qualitative interview to assess feasibility and acceptability, comprehension, comfort with screening questions, and preferences for screening mode (interviewer or computer). Qualitative data analysis organized the participants' feedback into major themes. Results: Participants overwhelmingly reported being comfortable with the ACASI ASSIST. Mean administration time was 5.2 minutes (range: 1.6–14.8 minutes). The major themes from the qualitative interviews were (1) ACASI ASSIST is feasible and acceptable to patients, (2) Social stigma around substance use is a barrier to patient disclosure, and (3) ACASI screening should not preclude personal interaction with providers. Conclusions: The ACASI ASSIST is an appropriate and feasible approach to substance use screening in primary care. Because of the highly sensitive nature of substance use, screening tools must explain the purpose of screening, assure patients that their privacy is protected, and inform patients of the opportunity to discuss their screening results with their provider.